Mutation - Gillespie, Stephen (Henry Stewart Talks, 2010)
Factors to study in the evolution of resistance, Antibiotic resistance by chromosomal mutation, Likelihood of resistance emerging, Determining mutation rate, Parameters for planning a mutation rate experiment, Methods of calculating mutation rate, Assumptions in a fluctuation analysis, Environmental stresses in the host environment, Hypermutability